Inhibitory control is not lateralized in Parkinson's patients. Issue 3 (March 2016) - Mirabella, G.; Giannini, G.; Modugno, N.
Abstract : Parkinson's disease (PD) is often characterized by asymmetrical symptoms, which are more prominent on the side of the body contralateral to the most extensive affected brain hemisphere. The effect of symptom laterality on the cognitive performance is not yet clear. However, lateralised PD presents an opportunity to examine the effects of asymmetric subcortical dopamine deficiencies on cognitive functioning. As it has been hypothesized that inhibitory control relies upon a right-lateralized pathway, we tested whether left-sided PD (LPD) patients suffer from more severe deficit in this key executive function than right-sided PD patients (RPD). To this aim, via a countermanding reaching task, we assessed both proactive and reactive inhibition in 27 LPD, RPD patients and 27 age-matched healthy subjects. As expected, we found that PD patients were significantly more impaired in both forms of inhibitory control than healthy subjects. Nevertheless, there were no differences between LPD and RPD patients. All in all, these data support the idea that brain regions affected by PD play a fundamental role in subserving inhibitory function, but do not sustain the hypothesis according to which this executive function is predominantly or solely computed by the brain regions of the right hemisphere.